The Experience of Type II Diabetes Mellitus Patients with Early Symptoms of Hypoglycemia: A Phenomenological Study - Nurjannah, Misbah; Asthiningsih, Ni Wayan Wiwin (Jurnal Keperawatan Soedirman, 2023)
Hypoglycemia is one of the acute complications that often occur in diabetes mellitus (DM) patients and could become an emergency condition that requires immediate treatment. The initial symptoms of hypoglycemia are cold sweats, tremors, dizziness, and blurred vision. Generally, DM patients’ lack of diet management exacerbates hypoglycemia. This study aimed to explore experience of type 2 diabetes patient’s hypoglycemia symptoms and affected factors. This qualitative research applied a phenomenological approach to seven participants. Semi-structured interviews were done to collect data. The Braun & Clarke method was then used to analyze the data. This study revealed three themes including the initial hypoglycemia symptoms, diet modification, and medication adherence. The study’s results are expected to provide information on the importance of education and control related to initial hypoglycemia symptoms, nutrition, and medications awareness to the type 2 diabetes patients and family.